Physicochemical Characterization and Antioxidant Properties of Essential Oils of M. pulegium (L.), M. suaveolens (Ehrh.) and M. spicata (L.) from Moroccan Middle-Atlas - Nadia Zekri; Hanane Elazzouzi; Atika Ailli; Aman Allah Gouruch; Fatima Zahrae Radi; Mohammed Alaoui El Belghiti; Touriya Zair; Gema Nieto; Juan A. Centeno; José M. Lorenzo (Foods, 2023)
The cosmetics and food fields are based on the use of synthetic substances to protect their products against oxidation. However, synthetic antioxidants were reported to have negative effects on human health. The interest to develop natural antioxidants from plants has been growing in recent decades. The aim of this study was to determine the antioxidant properties of three essential oils (EOs) of M. pulegium (L.), M. suaveolens (Ehrh.) and M. spicata (L.) from the Azrou and Ifrane regions. The organoleptic characteristics, yields and physical properties were determined for the selected EOs. Their chemical compositions were identified using GC-MS; then, their antioxidant activities were evaluated using the DPPH• free radical scavenging activity and were compared with the ascorbic acid standard. The determined physicochemical parameters of dry matter and EOs demonstrated their good quality. The analysis of the EOs showed the dominance of pulegone (68.86–70.92%) and piperitenone (24.81%), piperitenone oxide (74.69–60.3%), and carvone (71.56–54.79%) and limonene (10.5–9.69%) for M. pulegium, M. suaveolens and M. spicata, respectively, from Azrou and Ifrane. Additionally, the antiradical tests demonstrated the remarkable power of these EOs, especially M. pulegium EO (IC50 = 15.93 mg/mL), which recorded the best activity compared with ascorbic acid (IC50 = 8.849 mg/mL). The obtained results indicated that these EOs could be applied as natural antioxidants in the food industry.